An investigation on effect of quarry dust as sand replacement on compressive and flexural strength of foam concrete - Norazila, Kamarulzama (2010)
Foam concrete is a type of lightweight concrete which is lighter than conventional concrete. It is non-load bearing structural element which has lower strength than conventional concrete. Foam concrete is widely used in construction field and quite popular for some application because of its light weight such as reduction of dead load, non-structural partitions and thermal insulating materials. Because of its low strength, some material is used in order to increase the foam concrete strength. A study on the effect of quarry dust as sand replacement material on compressive and flexural strength of foam concrete was conducted. This study was conducted to determine the compressive strength and flexural strength of foam concrete by using quarry as partial sand replacement material. This report presents the feasibility of the usage of quarry dust as 10 %, 20 % and 30 % substitutes for sand in foam concrete. Mix design was developed for four different proportion of quarry dust in foam concrete. Tests were conducted on cubes and beams to study the strength of concrete made of quarry dust and results were compared with the control foam concrete. It is found that the compressive and flexural strength of foam concrete made of quarry dust are nearly 40 % more than the control foam concrete.